2023
DOI: 10.1039/d2qo01993k
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-mediated NHC and photoredox co-catalyzed 1,2-sulfonylacylation of allenesviaacyl and allyl radical cross-coupling

Abstract: Allyl radicals served as a crucial intermediate in the radical functionalization of fundamental raw materials and received increasing attention. Despite the significance, allyl-radicals-participated radical cross-couplings were rare and mainly focused...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Mechanistic studies indicated that the key step of the transformation was also the cross‐coupling between ketyl‐radical 40‐III and allenyl radical 40‐IV . Additionally, a robust radical 1,2‐sulfonylacylation of allenes was also achieved by the same group under nearly the same catalytic conditions (Scheme 40d) [58] . Therefore, a lot of valuable sulfonyl‐containing multi‐substituted allyl ketones 40‐10 could be produced under extremely mild conditions with excellent regioselectivity.…”
Section: Radical Acylation Of 13‐enynes and Allenes Via Nhc‐catalysismentioning
confidence: 89%
See 1 more Smart Citation
“…Mechanistic studies indicated that the key step of the transformation was also the cross‐coupling between ketyl‐radical 40‐III and allenyl radical 40‐IV . Additionally, a robust radical 1,2‐sulfonylacylation of allenes was also achieved by the same group under nearly the same catalytic conditions (Scheme 40d) [58] . Therefore, a lot of valuable sulfonyl‐containing multi‐substituted allyl ketones 40‐10 could be produced under extremely mild conditions with excellent regioselectivity.…”
Section: Radical Acylation Of 13‐enynes and Allenes Via Nhc‐catalysismentioning
confidence: 89%
“…Additionally, a robust radical 1,2sulfonylacylation of allenes was also achieved by the same group under nearly the same catalytic conditions (Scheme 40d). [58] Therefore, a lot of valuable sulfonyl-containing multi-substituted allyl ketones 40-10 could be produced under extremely mild conditions with excellent regioselectivity.…”
Section: Radical Acylation Of 13-enynes and Allenes Via Nhc-catalysismentioning
confidence: 99%
“…In 2023, the Zheng and Zhang group developed NHCs/PC dual-catalyzed radical 1,2-sulfonyl acylation of allenes 51-1 with sulfinates 51-3 and aroyl fluoride 51-2 (Scheme 51). 141 Extremely mild conditions allowed for a broad substrate scope and functional group tolerance. Similar to previous reports, in situ generated sulfonyl radicals 51-7 underwent regioselective addition to allenes generating allyl radicals 51-8 , which are trapped by persistent BIR affording sulfonyl-substituted olefins.…”
Section: Nhcs-catalyzed Radical α-Acylated Difunctionalizationmentioning
confidence: 99%
“…By replacing the 1,3-enyene acceptor of the sulfonyl radical with an allene, these investigators also achieved 1,2-sulfonylacylation of allenes to provide valuable sulfonyl-containing multisubstituted allyl ketones (Scheme 45). 50 3.2.3 Formation of phenyl radicals. Recently, the Studer group reported a C-H Acylation of arenes and heteroarenes through cooperative photoredox/NHC radical catalysis (Scheme 46).…”
Section: Ketyl Radicals Generated Via Acyl Azolium Intermediatesmentioning
confidence: 99%